A DOUBLE SPIKE FOR OSMIUM ANALYSIS OF HIGHLY RADIOGENIC SAMPLES - Markey R.; Hannah J.L.; Morgan J.W.; Stein H.J. (My University, 2003)
Geologic samples containing highly radiogenic Os (molybdenites and low-level, highly radiogenic (LLHR) samples) have no internal means by which to correct for mass fractionation during isotopic measurement by mass spectrometry. We describe a double spike for use with highly radiogenic samples, created by combining isotopically enriched 188Os and 190Os. Spiking molybdenite and other highly radiogenic minerals with this tracer allows for a fractionation correction, as well as a more reliable determination of common Os relative to analysis using single spikes.The precise isotopic composition of the double spike is determined by a calibration against natural Os, in which two separate measurements are necessary: one each for the pure double spike and the spike-standard mixture. An estimate of the true composition of the spike is obtained by least squares approximation, and the errors are obtained by Monte Carlo methods. Sample analyses are then much more straightforward than the calibration because isotopic compositions of all components are known a priori.Results obtained with a mixed Re-double Os spike demonstrate an improved reproducibility over individual 185Re and 190Os spikes. For an Archean in-house molybdenite standard we now observe a reproducibility of 0.08%. The ability to make a fractionation correction is essential for Os measurements made by ion counting. With the double Os spike, young samples and those with low Re contents (i.e., LLHR) can now be accurately analyzed. The 188Os-190Os double spike also allows a determination of the common Os contents of highly radiogenic samples. Common Os is poorly determined for ancient samples with high concentrations of 187Os, which fortunately are not sensitive to estimates of common Os. Common Os can be reasonably well determined for younger samples and those with low Re contents. We report a common Os concentration of 0.4+/-0.1 ppb for an 11 Ma molybdenite. Consideration of common Os content is important for age determination of young samples and LLHR samples, and is not possible by other published means of Os analysis.
Keywords: MOLYBDENITE; DATING; OSMIUM; DOUBLE SPIKE; MASS FRACTIONATION; HIGHLY RADIOGENIC; Archean; Precambrian::Archean; Докембрий::Архей